Histone acetylation modifications: A potential targets for the diagnosis and treatment of papillary thyroid cancer - Chen, Chongyang; Liu, Jingfang (Frontiers in Oncology, 2022)
Thyroid cancer is a common malignancy of the endocrine system, with papillary thyroid cancer (PTC) being the most common type of pathology. The incidence of PTC is increasing every year. Histone acetylation modification is an important part of epigenetics, regulating histone acetylation levels through histone acetylases and histone deacetylases, which alters the proliferation and differentiation of PTC cells and affects the treatment and prognosis of PTC patients. Histone deacetylase inhibitors induce histone acetylation, resulting in the relaxation of chromatin structure and activation of gene transcription, thereby promoting differentiation, apoptosis, and growth arrest of PTC cells.